Women’s Rights and Law Enforcement: A Family Law Perspective in Addressing Forced Marriage - Fauzia, Ana; Hamdani, Fathul; Nasution, Aulia Rosa (JURNAL AKTA, 2024)
Forced marriages are frequent in Indonesia for several reasons, including economics and culture. In reality, practically all South Asian countries have the same problem, with poverty and tribal animosity frequently being used to force certain adolescents to marry. The purpose of this study is to examine women’s rights in the context of family law in avoiding forced marriage, as well as to examine law enforcement against forced marriage from a family law viewpoint. This research uses normative legal methods with statutory, conceptual, case, and comparative approaches. The findings reveal that respect for and implementation of women’s rights have been included in various legal instruments, both at the international and state levels. The protection of women’s rights is critical for achieving substantive justice and avoiding forced marriage. However, the combination of social, cultural, and legal concerns continues to challenge law enforcement. As a result, a family consultancy institution in partnership with the judiciary is required, similar to Australia, which has a Family Court to address instances such as forced marriage. With consultants who understand family matters and are experts in their fields, the settlement of cases of forced marriage through non-litigation is expected to be more effective, where the results of the decision can be determined by the court, as is the practice in Australia.